Nano-silver compound hydrogel for promoting wound skin healing and repairing and preparation method of nano-silver compound hydrogel

By preparing nanosilver composite hydrogels, the photothermal effect of black phosphorus nanosheets and the antibacterial properties of nanosilver, combined with the three-dimensional network structure of quaternized chitosan and hyaluronic acid, the shortcomings of antibacterial properties and biocompatibility of wound healing materials in the prior art are solved, and efficient wound healing and antibacterial effects are achieved.

CN119838049APending Publication Date: 2025-04-18SHIHEZI UNIVERSITY
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202311354458.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-10-18
Publication Date
2025-04-18

AI Technical Summary

Technical Problem

There is a lack of effective materials in the prior art to promote healing and repair of wound skin, especially in the combination of antibacterial properties and biocompatibility.

Method used

By preparing a nano-silver composite hydrogel, the photothermal effect of black phosphorus nanosheets and the antibacterial properties of nano-silver are used to combine the three-dimensional network structure formed by quaternary chitosan and hyaluronic acid to improve adhesion and antibacteriality, thereby promoting wound healing.

Benefits of technology

It has achieved good drug loading ability and biocompatibility, significant antibacterial properties and ability to promote wound skin healing and repair, and the slow release of drug loading at physiological temperatures reduces the number of medications and has great application prospects.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure FT_3
    Figure FT_3
Patent Text Reader

Abstract

The invention discloses nano-silver compound hydrogel for promoting wound skin healing and repairing and a preparation method of the nano-silver compound hydrogel. The nano-silver compound hydrogel has good drug-loaded capacity, and meanwhile has the capacity of promoting wound skin healing and repairing. The prepared nano-silver compound hydrogel is smeared to a skin wound to seal the wound, and under the irradiation of 808 nm of near-infrared light, the nano-silver loaded on the black phosphorus nanosheet releases silver ions, so that the efficient antibacterial ability is achieved. In the gel system, the black phosphorus nanosheet is mixed with the hyaluronic acid and the quaternized chitosan to enhance the adhesion, and in addition, the photo-thermal effect of the black phosphorus nanosheet and the synergistic antibacterial effect are combined, so that the rapid healing and repair of a wound are promoted. The hydrogel obtained in the invention has good biocompatibility, and has potential application value in tissue engineering.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of biomedical materials, and in particular to a nano-silver composite hydrogel for promoting wound skin healing and repair and a preparation method thereof. Background Art

[0002] Hydrogel is a soft material with a high water content and a three-dimensional network structure, and its morphology is between solid and liquid. It is usually made of hydrophilic macromolecules or polymers cross-linked by covalent bonds, hydrogen bonds, van der Waals forces, etc. Good biocompatibility, predictable degradation rate, adjustable mechanical properties and good elasticity make hydrogel an excellent material for biomedical applications, and it has also become a research hotspot for biomedical materials in recent years.

[0003] In wound healing, hydrogels have controllable tissue adhesion, can provide a moist environment for wound skin healing, and can serve as a barrier to bacterial penetration and a matrix for drug delivery.

[0004] As a new type of two-dimensional material, black phosphorus has unique antibacterial advantages. The antibacterial activity generated by the photothermal effect is considered to be another safe and effective method for treating bacterial infections. Near-infrared light can penetrate deep into mammalian cells and cause little damage to normal cells. The heat generated by near-infrared light can inhibit the growth of bacteria and kill bacteria by changing the permeability of bacterial cell membranes and signal transmission pathways through an overheated environment. However, there are currently few applications of combining black phosphorus with hydrogels for therapeutic materials or drugs, especially in the preparation of materials that promote wound skin healing and repair.

[0005] The surface of nanosilver particles carries a positive charge, which binds to negatively charged cellulose through electrostatic interaction and is bound in the cellulose hydrogen bond network, giving cellulose a good antibacterial effect. There are many explanations for the antibacterial mechanism of nanosilver. When nanosilver is dissolved in water, it is converted into silver ions, which can then be used to kill pathogens. Nanosilver has a large specific surface area and ultra-small size. It can easily enter the cell body by destroying the cell membrane, and then be converted into silver ions in the cytoplasm to exert a highly effective antibacterial effect. Therefore, it has a good prospect in promoting wound skin healing and repair applications. Summary of the invention

[0006] Therefore, based on the above background, the first purpose of the present invention is to provide a nanosilver composite hydrogel for promoting wound skin healing and repair. The nanosilver composite hydrogel prepared by the present invention has good drug loading capacity and biocompatibility, and also has significant antibacterial properties and the ability to promote wound skin healing and repair.

[0007] The second purpose of the invention of this application is to provide a method for preparing a nano-silver composite hydrogel for promoting wound skin healing and repair.

[0008] In order to achieve the first purpose of the invention of this application, the technical solution adopted is to prepare nanosilver composite hydrogel.

[0009] In order to achieve the second purpose of the invention of this application, the technical solution adopted is: S1: Preparation of black phosphorus nanosheet dispersion; S2: dispersion of nanosilver particles treated with silver nitrate; S3: taking a black phosphorus nanosheet dispersion liquid, adding a nanosilver dispersion liquid thereto, to obtain a black phosphorus nanosheet solution loaded with nanosilver; S4: The quaternized chitosan sol and the hyaluronic acid sol are mixed, and then the black phosphorus nanosheet solution is mechanically poured in, vortexed, and mixed evenly to obtain the nanosilver hydrogel loaded on the black phosphorus nanosheet.

[0010] Preferably, in step S1, the black phosphorus powder is fully ground in a mortar, and the ground black phosphorus powder is dissolved in N-methylpyrrolidone, centrifuged, ultrasonicated, and washed with ultrapure water to obtain a black phosphorus nanosheet dispersion.

[0011] More preferably, the black phosphorus powder is obtained by fully grinding in an agate mortar.

[0012] Preferably, in step S1, the centrifugation conditions are 10000-13000 rpm / min, 20-30 min, and 4° C. Low temperature conditions can reduce the degradation rate of black phosphorus nanosheets.

[0013] More preferably, the centrifugation conditions are 12000 rpm / min, 20 min, 4°C.

[0014] Preferably, in step S1, the ultrasonic time is 6 hours, in order to split the larger black phosphorus nanosheets into smaller black phosphorus nanosheets through molecular collision and the like.

[0015] Preferably, in step S1, ultrapure water washing is performed three times to remove black phosphorus nanosheets with larger particle sizes.

[0016] Preferably, in step S2, a silver nitrate solution is taken, a polyvinyl pyrrolidone (PVP) solution is added; magnetic stirring is applied, and an ammonium formate solution is added under stirring; aging is performed, ultrasonic re-dispersion is performed, the mixture is shaken, centrifuged, the supernatant is removed, and ultrapure water is added for washing, and the process is repeated until the supernatant has no obvious color, and the prepared nanosilver dispersion is obtained.

[0017] Preferably, in step S2, the silver nitrate solution, the polyvinyl pyrrolidone solution and the ammonium formate solution are reacted and aged under light-proof conditions.

[0018] Preferably, in step S2, the ammonium formate solution is slowly added under stirring to allow it to react fully.

[0019] Preferably, in step S2, the silver nitrate solution, the polyvinyl pyrrolidone solution and the ammonium formate solution are magnetically stirred for 2 hours to allow them to react with each other to generate nanosilver crystal nuclei.

[0020] Preferably, in step S2, the silver nitrate solution, the polyvinyl pyrrolidone solution and the ammonium formate solution are aged for 3 hours and 30 minutes to allow the nanosilver nuclei to grow to a suitable size.

[0021] Preferably, in step S2, the centrifugation conditions are 8500 rpm / min, 20 min, and 20°C.

[0022] Preferably, in step S3, the black phosphorus nanosheet dispersion and the nanosilver dispersion are uniformly mixed in a mass ratio of 1:10 and ultrasonicated for 30 minutes.

[0023] Preferably, in step S3, the black phosphorus nanosheet dispersion and the nanosilver dispersion are ultrasonicated and then shaken.

[0024] Preferably, in step S3, the shaking conditions are 250 rpm / min, 12 h, and 10°C.

[0025] Preferably, in step S4, the mass concentration of the quaternized chitosan sol is 12.5%, and the mass concentration of the hyaluronic acid sol is 3.75%.

[0026] Preferably, in step S4, the volume ratio of the quaternized chitosan sol to the hyaluronic acid sol is 6:4.

[0027] Preferably, in step S4, the volume ratio of the black phosphorus nanosheet dispersion to the hydrogel is 1:10.

[0028] The present invention also provides the use of the above-mentioned nanosilver complex hydrogel for promoting wound skin healing and repair in skin wound healing and repair drugs.

[0029] The invention of the present application adopts quaternized chitosan and hyaluronic acid to form a three-dimensional network structure of the hydrogel, which plays a role in increasing adhesion.

[0030] Quaternary ammonium chitosan is a water-soluble cationic polymer containing quaternary ammonium groups in its molecular structure. It contains amino and hydroxyl groups and can form hydrogen bonds. This type of polymer not only retains some of the excellent properties of chitosan itself, but also improves its water solubility. Hyaluronic acid molecules contain a large number of carboxyl and hydroxyl groups, which form intramolecular and intermolecular hydrogen bonds in aqueous solution, which makes it have a strong water-retaining effect and can bind to the protonated amino NH 3 + Cross-linking is achieved through electrostatic interactions to form a three-dimensional gel network.

[0031] The nano-silver composite hydrogel prepared by the present invention is applied to the skin wound to seal the wound. Under the near-infrared 808nm irradiation, the skin surface temperature rises rapidly, and the nano-silver on the black phosphorus nano-sheet releases silver ions to exert efficient antibacterial ability.

[0032] The above technical solution has the following beneficial effects: (1) The black phosphorus nanosheets in the present invention utilize photothermal effect and photodynamic effect to generate photothermal damage to bacteria. The photodynamic effect can generate ROS. The oxidative stress caused by ROS is the main mechanism of bacterial death. These ROS kill bacterial pathogens by destroying cell membranes, intracellular molecules of bacteria such as DNA, RNA and protein interactions. There is also membrane damage caused by physical destruction, and the physical destruction of bacterial membranes using rough surfaces and sharp edges is considered to be a nanoknife mechanism. In addition, under the irradiation of a wavelength of 808nm, the photothermal effect of black phosphorus nanosheets and nanosilver can produce a synergistic antibacterial effect. In the gel system, quaternized chitosan and hyaluronic acid are added to improve the adhesion and antibacterial properties of the system, which can better promote the healing of skin wounds. In the process of use, the gel at physiological temperature slowly releases the loaded drug as the black phosphorus nanosheets slowly degrade, which can reduce the number of medications. In vivo experimental results show that the nanosilver hydrogel loaded on black phosphorus nanosheets can promote rapid wound healing and has great application prospects in wound treatment. (2) Compared with other existing wound-promoting hydrogels, in addition to the photothermal and photodynamic effects and nanoknife mechanism of black phosphorus, the loaded nanosilver and the quaternary ammonium chitosan mixed with it have certain antibacterial properties, good biocompatibility, easy degradation, and will not cause damage to the body's organs. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] In order to more clearly illustrate the embodiments of the invention of the present application or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the invention of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work. Figure 1 It is a low-magnification transmission electron microscopy (TEM) image of BP and BP-AgNPs in Example 5 of the present invention; Figure 2 This is a scanning electron microscope image (SEM) of BP-AgNPs@Gel in Example 6 of the present invention; Figure 3Fourier transform infrared spectra (FITR) of six samples of BP, QCS, HA, BP-AgNPs, Gel, and BP-AgNPs@Gel in Example 7 of the present invention; Figure 4 Graph showing the blood compatibility of Gel and BP-AgNPs@Gel in Example 8 of the present invention; FIG5 is a graph showing the antibacterial performance of Gel and BP-AgNPs@Gel in Example 9 of the present invention against Escherichia coli and Staphylococcus aureus; FIG. 6 is a diagram showing the wound skin repair conditions and Masson collagen deposition content of different groups in Example 10 of the present invention. DETAILED DESCRIPTION

[0034] In order to make the purpose, technical solution and advantages of the embodiments of the invention of this application clearer, the technical solution in the embodiments of the invention of this application will be clearly and completely described below in conjunction with the drawings in the embodiments of the invention of this application. Obviously, the described embodiments are part of the embodiments of the invention of this application, rather than all the embodiments. Based on the embodiments of the invention of this application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the invention of this application.

[0035] Unless otherwise specified, the experimental methods used in the following examples are conventional methods.

[0036] Unless otherwise specified, the materials and reagents used in the following examples can be obtained from commercial sources.

[0037] The invention of the application is further described below with reference to the accompanying drawings.

[0038] Example 1: Preparation of black phosphorus nanosheet dispersion

[0039] First, 4 mg of black phosphorus powder was weighed and ground thoroughly in a mortar. The ground black phosphorus powder was dissolved in 2 mL of N-methylpyrrolidone (NMP) and placed in an ultrasonic cleaner for 6 hours (ultrasonication for 5 minutes, vortexing for 2 minutes). Then, it was centrifuged for 30 minutes (2000 rpm, 4°C) to remove the unpeeled large-sized black phosphorus and collect the supernatant. The supernatant was placed in an empty centrifuge tube and centrifuged for another 20 minutes (12000 rpm, 4°C). 1 mL of ultrapure water was added, and the prepared black phosphorus nanosheet solution (BP dispersion) was wrapped with tin foil. The solution was stored below 4°C.

[0040] Example 2: Preparation of Nanosilver Particle Dispersion Treated with Silver Nitrate

[0041] First, 106.4 mg of silver nitrate powder was accurately weighed and dissolved in 8 mL of ultrapure water to form a silver nitrate solution, then 234 mg of polyvinyl pyrrolidone (PVP) powder was accurately weighed and dissolved in 8 mL of ultrapure water to form a PVP solution, and then 234 mg of ammonium formate powder was accurately weighed and dissolved in 8 mL of ultrapure water to form an ammonium formate solution. The silver nitrate solution and the PVP solution were mixed, and the ammonium formate solution was slowly dripped into the mixed solution while stirring, and placed on a magnetic stirrer for stirring (300 rpm / min, 2 h). After the magnetic stirring was completed, it was aged for 3 hours and 30 minutes, placed in an ultrasonic cleaner for 1 h, and the mixed solution was placed in an empty centrifuge tube, centrifuged for 20 minutes (8500 rpm, 25 ° C), the supernatant was removed, 1 mL of ultrapure water was added, and centrifuged again under the same conditions, the supernatant was removed, anhydrous ethanol was added to the precipitate, centrifuged, 1 mL of ultrapure water was added, and the prepared nanosilver solution (AgNPs solution) was wrapped with tin foil and stored at room temperature.

[0042] Example 3: Take a black phosphorus nanosheet dispersion liquid, add a nanosilver dispersion liquid thereto, and obtain a black phosphorus nanosheet solution loaded with nanosilver;

[0043] Take the black phosphorus nanosheet dispersion, centrifuge it at 12000rpm for 200min, remove the supernatant, then add the nanosilver solution with a mass ratio of 10 times that of the black phosphorus nanosheets, shake it on a temperature-controlled shaker in the dark (speed 250rpm, temperature 10℃) for 12h, centrifuge it at 10000rpm for 15min to remove the free nanosilver, retain the supernatant, precipitate it as BP@AgNPs, that is, the black phosphorus nanosheet solution loaded with nanosilver, wrap it with tin foil, and store it at 4℃.

[0044] Example 4: The quaternized chitosan sol and the hyaluronic acid sol are mixed, and then the black phosphorus nanosheet solution is mechanically poured in, vortexed, and mixed evenly to obtain the nanosilver composite hydrogel.

[0045] Preparation of quaternized chitosan sol

[0046] 0.5 g of quaternary ammonium chitosan powder was accurately weighed and added to 4 mL of ultrapure water, and stirred to form a sol state, thereby obtaining a quaternary ammonium chitosan sol with a mass concentration of 12.5%.

[0047] Preparation of hyaluronic acid sol

[0048] 0.3375 g of hyaluronic acid powder was accurately weighed and added to 9 mL of ultrapure water, and stirred to form a sol state, thereby obtaining a hyaluronic acid sol with a mass concentration of 3.75%.

[0049] Preparation of Nanosilver Composite Hydrogel

[0050] The quaternized chitosan sol and the hyaluronic acid sol were prepared in a volume ratio of 6:4, and the volume ratio of the black phosphorus nanosheets to the hydrogel was 1:10. They were prepared at room temperature, mixed and stirred for a period of time until they were completely mixed. After mixing, they were wrapped with tin foil and stored at 4°C.

[0051] Characterization, biocompatibility and skin wound healing performance evaluation of black phosphorus nanosheets (BP), drug (nanosilver) loaded black phosphorus nanosheets (BP@AgNPs), and nanosilver composite hydrogel (BP@AgNPs-Gel).

[0052] Example 5: TEM Characterization of Black Phosphorus Nanosheets and Black Phosphorus Nanosheets Loaded with Nanosilver

[0053] The microstructure of the samples was observed using a field emission transmission electron microscope with an accelerating voltage of 200 kV.

[0054] Sample preparation: ultrasonically disperse the sample in anhydrous ethanol, dilute it to a certain concentration, take a drop (20 μL) and drop it on the copper mesh loaded with carbon film, wipe the edge with clean filter paper, dry it at room temperature, and observe it under field emission transmission electron microscopy.

[0055] Results Figure 1 Figure A is a transmission electron microscope image of black phosphorus nanosheets. Black phosphorus is a one-layer or several-layer sheet structure with a uniform particle size of about 200-400nm. Figure B is a transmission electron microscope image of black phosphorus nanosheets loaded with nanosilver. The nanosilver is black round particles with a particle size of about 50-100nm. In the figure, black particles can be clearly seen on the black phosphorus nanosheets, indicating that the nanosilver particles are successfully loaded on the black phosphorus nanosheets.

[0056] Example 6: SEM Characterization of BP@AgNPs-Gel

[0057] The BP@AgNPs-Gel sample was placed in liquid nitrogen for freezing and then freeze-dried. After the water was removed, the hydrogel sample was cut and then coated with gold to observe the microstructure of the cross-section surface. The microstructure of the freeze-dried gel was observed using a scanning electron microscope.

[0058] like Figure 2 The figure shows the scanning electron micrograph of the BP@AgNPs-Gel sample. As can be seen from the figure, the hydrogel presents a three-dimensional network structure with high porosity and dense consistency.

[0059] Example 7: FITR spectra of four samples

[0060] Purified BP (black phosphorus nanosheet dispersion), BP@AgNPs (black phosphorus loaded nanosilver solution), QCS (quaternized chitosan), HA (hyaluronic acid) powders and freeze-dried Gel and BP-AgNPs@Gel sample powders were pressed with KBr dry powder, and the infrared spectra of the samples were measured by Fourier transform infrared spectrometer with a scanning wave number range of 4000-400 cm -1 , resolution 4cm -1 The blank solvent of the solution was dimethyl sulfoxide.

[0061] like Figure 3 As shown, at 1478cm -1 There is a characteristic peak of the methyl group of QCS ammonium ion at 3440 cm -1 The band has the vibration peaks of OH and NH stretching of HA, and in BP-AgNPs@Gel, 3450cm -1 Blue shift to 3410 cm -1 The amino and hydroxyl groups of QCS form hydrogen bonds with the hydroxyl groups of HA, reducing the electron cloud density of OH and NH. In the BP@AgNPs spectrum, 1385cm -1 There is a new peak at 3 - Typical infrared spectra of AgNPs in AgNO 3 Reduction of Ag in saturated solution + At 1610cm -1 The characteristic peaks of -NH 2 The angular vibration of BP and BP-AgNPs@Gel at 629 cm -1 There is an infrared absorption peak of PO in all bands.

[0062] Example 8: Blood compatibility evaluation

[0063] The blood compatibility of BP-AgNPs@Gel was evaluated by in vitro hemolysis experiment. Red blood cells were separated from mouse blood by centrifugation at 2500rpm for 5min, and the red blood cells were washed several times with 0.9% saline until the supernatant was colorless. 500μL of 5% red blood cell suspension was added to a 1.5mL centrifuge tube containing 500μL of hydrogel pre-treated with 0.9% saline, and then the centrifuge tube was placed in a 37℃ constant temperature incubator for 3h. After that, the liquid in the centrifuge tube was centrifuged at 2500rpm, 5min, 4℃, and then 300μL of the supernatant was transferred to a 96-well plate and its absorbance value at 540nm was measured. The hemolysis rate was calculated according to the formula: Hemolysis rate (%) = [(A p -A b) / (A t -A b )]×100% Among them, A p is the absorbance value of the supernatant, A t is the absorbance value of the 0.1% Triton x-100 positive control, A b It is the absorbance value of 0.9% saline negative control. 200μg / mL, 100μg / mL, 50μg / mL, 10μg / mL represent that 1mL black phosphorus loaded silver nano-hydrogel contains 200μg, 100μg, 50μg, 10μg black phosphorus nanosheets, respectively.

[0064] like Figure 4 As shown, the supernatant of the Gel group, 200μg / mL, 100μg / mL, 50μg / mL, and 10μg / mL groups showed a light yellow color similar to the 0.9% saline negative control group, with only slight hemolysis; while 1% Triton x-100 showed a bright red color, indicating a severe hemolytic reaction. The quantitative data (with 1% Triton x-100 as 100%) also showed that the Gel group, 200μg / mL, 100μg / mL, 50μg / mL, and 10μg / mL groups were all below the upper limit of hemolysis of 5%. The above results show that BP-AgNPs@Gel has good blood compatibility and can be used safely in vivo.

[0065] Example 9: Evaluation of antibacterial properties

[0066] First, the antibacterial properties of BP-AgNPs@Gel were studied by counting the colony growth of the bacterial co-culture hydrogel plate. The experimental groups were divided into blank group (control, n = 3), pure gel group (Gel, n = 3), pure gel illumination group (Gel + NIR, n = 3), nanosilver complex hydrogel group (BP@AgNPs-Gel, n = 3) and nanosilver complex hydrogel illumination group (BP@AgNPs-Gel + NIR, n = 3). After the samples of different groups were treated with a bacterial suspension with an absorbance of 0.1, they were co-incubated for 3h30min under dark conditions, and 100μL of the sample was applied to a Luria-Bertani (LB) culture dish, placed in an incubator at 37℃, inverted for 24h, and the colony growth was observed. According to the colony growth of each group, the colonies were counted, and the difference in bacterial survival rate was drawn with the blank group as the control.

[0067] As shown in Figure 5, the results demonstrated that BP@AgNPs-QCS-HA hydrogel had antibacterial activity. The antibacterial effect was further enhanced after light treatment (BP@AgNPs-Gel+NIR).

[0068] Quantitative analysis showed that the bacterial survival rates of Escherichia coli on Gel and Gel+NIR were 59.8% and 34.8%, respectively, and the bacterial survival rates of Staphylococcus aureus on Gel and Gel+NIR were 39.6% and 24.8, respectively. The bacterial survival rates of BP@AgNPs-Gel and BP@AgNPs-Gel+NIR were lower (12.8% and 5.4%, respectively), and the bacterial survival rate of hydrogels against Staphylococcus aureus also showed a similar trend (9.98% and 2.71%, respectively).

[0069] The antibacterial effect of near-infrared laser irradiation alone on Escherichia coli was not obvious, and a similar trend was observed for Staphylococcus aureus. The study showed that BP@AgNPs-Gel effectively and significantly inhibited the growth of Gram-positive and Gram-negative bacteria. BP@AgNPs-Gel exhibited significant antibacterial activity, which may be due to the synergistic effect of QCS, BP and AgNPs.

[0070] Example 10: Evaluation of wound skin healing

[0071] Grouping and treatment of experimental animals

[0072] Animal breeding environment

[0073] Barrier level: SPF level; temperature: 23±2℃; relative humidity: 50±10%; environmental noise: ≤60dB; provide sufficient feeding feed and drinking water.

[0074] Experimental animal groups: 50 SD male rats, weighing 180-220 g, were equally divided into 5 groups, including model group (control, n = 10), pure gel group (Gel, n = 10), pure gel illumination group (Gel + NIR, n = 10), nanosilver hydrogel group (BP@AgNPs-Gel, n = 10) and nanosilver hydrogel illumination group (BP@AgNPs-Gel + NIR, n = 10).

[0075] Since the blank control group (healthy mice without modeling) is generally used to determine whether the modeling is successful, and this experiment is a rat skin full-thickness trauma model with a high success rate, there is no need to set a blank control group. The model group was given normal saline, and the health status of the rats was observed daily during the feeding period and the weight changes were recorded.

[0076] Establishment of full-thickness excision model: After 7 days of animal experiment in the new environment, the animal model was established. Fasting for 12-16 hours, the rats were anesthetized by intraperitoneal injection of 10% chloral hydrate solution, and the injection volume was 0.3ml / 100g. The hair on the back of the rats was removed with a household pet electric shaver, and the hair that was not shaved was removed with a depilatory cream. After waiting for 20 minutes, the residual depilatory cream on the skin was wiped with saline, and the skin was disinfected with iodine solution. A disposable medical punch biopsy instrument (inner diameter of 1cm) was used to make a full-thickness circular excision wound. The day of modeling was regarded as day 0, and the wound surface was photographed for record. After punching, all rats in different groups were treated as soon as possible, and then placed in a clean mouse cage to allow them to recover on their own. They were kept in a single cage to prevent rats from biting each other's skin. From the first day after modeling, gel was applied to the rats at the same time every day. When applying gel and irradiating the wound locally, try not to pull the wound site to cause secondary injury. Wound surface photography and sampling were performed in batches on days 1, 4, 7, 11, and 14 after modeling.

[0077] Wound healing rate in rats

[0078] One, four, seven, eleven and fourteen days after treatment, the wounds were photographed with a digital camera and recorded with a ruler. Photoshop 2020 and Image-Pro Plus 6.0 software were used to calculate the wound area of ​​the rats to calculate the healing rate, and the wound healing time of the rats, that is, the time from wound formation to complete scab healing, was calculated. The calculation formula is: Wound healing rate (%) = [(A 0 -A t )÷A 0 ]×100% Among them, A 0 is the original wound area, cm 2 ; A t is the existing wound area, cm 2 .

[0079] like Figure 6-1 As shown, it is divided into five groups, control group, Gel group, Gel+NIR group, BP@AgNPs-Gel group and BP@AgNPs-Gel+NIR group. It can be seen from the figure that compared with other groups, the BP@AgNPs-Gel+NIR group can promote wound healing faster.

[0080] Masson collagen deposition content chart

[0081] Dewaxing to water: rinse the sections with xylene 3 times, 5 minutes each time; rinse the sections with anhydrous ethanol 2 times, 10 minutes each time; rinse the sections with 95%-80%-70% ethanol, 10 minutes each time; moisten the sections in PBS 2 times, 5 minutes each time.

[0082] Hematoxylin staining of cell nuclei: Stain with Weigert's iron hematoxylin in the Masson staining kit for 5 minutes, rinse continuously with water to remove free hematoxylin stain, differentiate with differentiation solution (1% hydrochloric acid ethanol) for 30 seconds, rinse continuously with water for about several minutes to remove the differentiation solution attached to the surface of the slice, and use anti-blue solution (0.6% ammonia water) to return to blue. Place the slice under a microscope to observe the staining. If the staining is not sufficient, repeat the operation until it meets the requirements.

[0083] Ponceau staining: Stain with the Ponceau acid fuchsin dye in the Masson staining kit for about 6 minutes, rinse continuously with distilled water to remove free Ponceau acid fuchsin dye, and place the sections under a microscope to observe the staining. If the staining is not sufficient, repeat the operation until it meets the requirements.

[0084] Phosphomolybdic acid treatment: Soak in the phosphomolybdic acid aqueous solution in the Masson staining kit for about 4 minutes.

[0085] Aniline blue staining: Do not wash with water. Directly counterstain with the aniline blue solution in the Masson staining kit for 5 minutes. Place the sections under a microscope to observe the staining. If the staining is not sufficient, counterstain until it meets the requirements.

[0086] Differentiation: Place the slices in a culture dish filled with 1% glacial acetic acid for 1 min.

[0087] Sealing: Dehydrate the sections by placing them in anhydrous ethanol and xylene three times, and then seal them with neutral gum.

[0088] Microscopic observation: The color change of collagen deposition during wound healing was observed under a microscope, and the collagen fibers appeared blue.

[0089] Masson staining was used to evaluate collagen fibers during wound healing. Figure 6-2 and 6-3As shown in the figure, on the 7th day, the collagen volume fractions of the control group, Gel group, Gel+NIR group, BP@AgNPs-Gel group and BP@AgNPs-Gel+NIR group were 22.85±1.62%, 36.99±4.48%, 50.57±0.18%, 57.38±0.49% and 66.09±2.12%. On the 14th day, the collagen volume fractions of the control group, Gel group, Gel+NIR group, BP@AgNPs-Gel group and BP@AgNPs-Gel+NIR group were 32.51±1.61%, 48.85±3.13%, 59.48±6.83%, 63.20±1.49% and 78.38±4.62%. Collagen deposition was observed in all groups on the 7th and 14th days. Compared with other groups, the collagen deposition in the wound of the control group was less. The collagen density of the wound surface treated with BP@AgNPs-Gel+NIR group was the highest, the fiber structure was the most orderly, and the collagen fibers were denser, thicker, and better arranged, similar to normal skin ( Figure 6-2 ). The collagen volume fraction in the BP@AgNPs-Gel+NIR group was the highest ( Figure 6-3 ). This indicates that BP@AgNPs-Gel+NIR can significantly promote collagen deposition during wound healing.

[0090] The present invention and its embodiments are described above, and such description is not restrictive. The drawings show only one embodiment of the present invention, and the actual structure is not limited thereto. In short, if ordinary technicians in the field are inspired by it, without departing from the purpose of the invention, they can design a structure and embodiment similar to the technical solution without creativity, which should belong to the protection scope of the present invention.

Claims

1. A nanosilver composite hydrogel, characterized in that: The invention comprises the following components: quaternary ammonium chitosan, hyaluronic acid and black phosphorus nanosheets, wherein the black phosphorus nanosheets are loaded with nano silver particles; and the mass ratio of quaternary ammonium chitosan: hyaluronic acid: black phosphorus nanosheets is 75:15:0.

1.

2. The method for preparing a nano-silver composite hydrogel according to claim 1, characterized in that: The method comprises the following steps: dissolving quaternized chitosan, hyaluronic acid and black phosphorus nanosheets in deionized water, and preparing nano silver composite hydrogel by physical mixing.

3. The method for preparing a nano-silver composite hydrogel according to claim 1, characterized in that: The nano silver particle dispersion is treated with silver nitrate; the mass ratio of black phosphorus nano sheets to nano silver particles is 1:

10.

4. The nanosilver composite hydrogel according to claim 1, characterized in that: The hydrogel is made of quaternary ammonium chitosan sol with a mass concentration of 12.5% ​​and hyaluronic acid sol with a mass concentration of 3.75%; the volume ratio of the quaternary ammonium chitosan sol to the hyaluronic acid sol is 6:

4.

5. The nanosilver composite hydrogel according to claim 3, characterized in that: The particle size of the black phosphorus nanosheets is 200-400nm; the particle size of the nanosilver particles is 50-100nm.

6. The method for preparing a nano-silver composite hydrogel according to any one of claims 1 to 4, characterized in that: The steps include: S1: Preparation of black phosphorus nanosheet dispersion; S2: dispersion of nanosilver particles treated with silver nitrate; S3: taking a black phosphorus nanosheet dispersion liquid, adding a nanosilver dispersion liquid thereto, to obtain a black phosphorus nanosheet solution loaded with nanosilver; S4: The quaternized chitosan sol and the hyaluronic acid sol are mixed, and then the black phosphorus nanosheet solution is mechanically poured in, vortexed, and mixed evenly to obtain the nanosilver composite hydrogel.

7. The method for preparing a nano-silver composite hydrogel according to claim 6, characterized in that: The preparation of the black phosphorus nanosheet dispersion in step S1 is as follows: 1) Grinding black phosphorus powder in a mortar, dissolving the ground black phosphorus powder in N-methylpyrrolidone, centrifuging, and washing with ultrapure water to obtain a black phosphorus nanosheet dispersion; The preparation of the nano silver particle dispersion in step S2 is as follows: 1) Take a silver nitrate solution, add a polyvinyl pyrrolidone (PVP) solution; stir magnetically, and then slowly add an ammonium formate solution under stirring; age, re-disperse by ultrasound, shake, centrifuge, remove the supernatant, wash with ultrapure water, repeat until the supernatant has no obvious color, and the prepared nanosilver dispersion is obtained.

8. The method for preparing a nano-silver composite hydrogel according to claim 6, characterized in that: The volume ratio of the black phosphorus nanosheet dispersion to the hydrogel is 1:

10.

9. Use of the nanosilver composite hydrogel according to any one of claims 1 to 8 in the preparation of wound skin healing and repair drugs.

Citation Information

Cited By

  • Preparation method of natural polysaccharide-based organic / inorganic hybrid photo-thermal antibacterial hydrogel

    CN121695323A